Evaluation of the physical properties of fluorescent carbon nanodots synthesized using Nerium oleander extracts by microwave-assisted synthesis methods - Simsek, Sinem; Alas, Melis Ozge; Ozbek, Belma; Genc, Rukan (ELSEVIER, 2019)
Rapid and one-step green synthesis of carbon nanodots (CDs) from Nerium oleander leaves was accomplished via domestic microwave oven and microwave-assisted hydrothermal synthesizer under various physical conditions. Effects of the synthesizer system, extract type depending on the solvents used in plant extraction, and synthesis conditions; such as reaction time, reaction temperature, surface passivation agent inclusion into the reaction medium, on the physicochemical properties and optical feature of CDs were investigated. The impacts of relevant conditions on CDs feature were determined clearly via UV-visible spectrophotometry, fluorescence spectrophotometry, dynamic light scattering analysis, and Fourier transform infrared spectroscopy. According to the results, while the most effective parameter on the fluorescence feature of CDs was determined as the presence of surface passivation agent (polyethylene glycol, PEG), the alteration in the fluorescence intensity depending on the reaction time and the reaction temperature was also observed. It was reported that the synthesis system and PEG existence in the reaction medium were more effective than the other inspected parameters on the hydrodynamic particle size, in general. Under optimum conditions, nanoparticles with a hydrodynamic size of less than 5 nm were obtained. The surface zeta potential charges of all particles were found as negative. While the extract type was significantly effective on the surface zeta potential of CDs synthesized by domestic microwave oven, the reaction temperature was found to be significant for the ones synthesized via microwave-assisted hydrothermal synthesis. (C) 2019 The Authors. Published by Elsevier B.V.
Keywords: Carbon nanodots; Fluorescent nanoparticles; Nerium oleander; Microwave synthesis; Microwave-assisted hydrothermal synthesis; Surface passivation; ONE-STEP SYNTHESIS; ECO-FRIENDLY SYNTHESIS; GREEN SYNTHESIS; QUANTUM DOTS; HYDROTHERMAL SYNTHESIS; LEAVES; PHOTOLUMINESCENCE; NANOPARTICLES; PYROLYSIS; PRECURSORS; Materials Science; Metallurgy & Metallurgical Engineering